2017
DOI: 10.1016/j.ijfoodmicro.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanisms involved in the bioprotective effect of Lactobacillus harbinensis K.V9.3.1.Np against Yarrowia lipolytica in fermented milk

Abstract: The use of lactic acid bacteria (LAB) as bioprotective cultures can be an alternative to chemical preservatives or antibiotic to prevent fungal spoilage in dairy products. Among antifungal LAB, Lactobacillus harbinensis K.V9.3.1Np showed a remarkable antifungal activity for the bioprotection of fermented milk without modifying their organoleptic properties (Delavenne et al., 2015). The aim of the present study was to elucidate the action mechanism of this bioprotective strain against the spoilage yeast Yarrowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Several studies were conducted using a targeted approach on the antifungal activity of L. harbinensis K.V9.3.1Np to assess the active biomolecules ( Belguesmia et al, 2014 ; Mieszkin et al, 2017 ). The obtained results suggested that acetic, lactic, hexanoic 2-hydroxybenzoic, and 2-pyrrolidone-5-carboxylic acids, acted as antifungal compounds but other antifungal agents, not targeted in these studies, could be involved in the high antifungal potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were conducted using a targeted approach on the antifungal activity of L. harbinensis K.V9.3.1Np to assess the active biomolecules ( Belguesmia et al, 2014 ; Mieszkin et al, 2017 ). The obtained results suggested that acetic, lactic, hexanoic 2-hydroxybenzoic, and 2-pyrrolidone-5-carboxylic acids, acted as antifungal compounds but other antifungal agents, not targeted in these studies, could be involved in the high antifungal potential.…”
Section: Resultsmentioning
confidence: 99%
“…In fermented yogurt, the antifungal activity was not affected through the storage and the technological processes indicating its adequacy as a substitute to chemical additives ( Delavenne et al, 2013 ). In separate reports, Belguesmia et al (2014) and Mieszkin et al (2017) quantified and tested several organic acids produced by L. harbinensis K.V9.3.1Np , such as acetic, lactic, hexanoic, 2-hydroxybenzoic, and 2-pyrrolidone-5-carboxylic acids. These compounds were shown to constitute part of the overall antifungal activity of the strain by acting in synergy with other, yet unidentified antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“… Al-Gamal et al (2019) reported that inhibitory effect of L. plantarum DSA20174 and Lactobacillus helveticus CNRZ32 on the growth of C. parapsilosis , isolated from Egyptian Feta-type cheeses, was related to excessive production of organic acids by LAB. The recent mechanistic studies in fermented milk and yogurt demonstrated that S. harbinensis K.V9.3.1Np produces both polyamines and organic acids (acetic, lactic, 2-pyrrolidone-5-carboxylic, hexanoic, benzoic, and 2-hydroxybenzoic), leading to membrane disruption and cell lysis of Y. lipolytica ( Delavenne et al, 2015 ; Mieszkin et al, 2017 ; Mosbah et al, 2018 ). McNair et al (2018) isolated and characterized a bioactive peptide (DMPIQAFLLY) derived from β-casein in sour cream added bioprotective cultures ( L. paracasei CH127 and L. rhamnosus CH126).…”
Section: Bio-protective Cultures and Other Yeast Interactionsmentioning
confidence: 99%
“…They include other organic acids (hydrocinnamic acid, dl -β-phenyllactic acid, dl -β-hydroxyphenyllactic acid, polyporic acid, azelaic acid, 2-hydroxybenzoic acid , 4-hydroxybenzoic acid, p -coumaric acid, vanillic acid, caffeic acid, succinic acid, 2-pyrrolidone-5-carboxylic acid), fatty acids (decanoic acid, 3-hydroxydecanoic acid, ( S )-(−)-2–hydroxyisocapric acid, coriolic acid, ricinoleic acid), cyclopeptides [cyclo(L-Pro-L-Pro), cyclo(L-Leu-L-Pro), cyclo(L-Tyr-L-Pro), cyclo(L-Met-L-Pro), cyclo(Phe-Pro), cyclo(Phe-OH-Pro), cyclo(L-Phe-L-Pro), cyclo(L-Phe-trans-4- OH-L-Pro), cyclo(L-His-L-Pro), and cyclo(Leu-Leu)], reuterin, hydrogen peroxide, and volatile compounds such as diacetyl [ 101 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ]. For example, Miezkin et al (2017) [ 175 ] attributed the antifungal effect of L. harbinensis K.V9.3.1.Np to the synergistic action of acetic, lactic, 2-pyrrolidone-5-carboxylic, ( S )-(−)-2–hydroxyisocapric, and 2-hydroxybenzoic acids, while Aunsbjerg et al (2015) [ 101 ] showed that increased production of diacetyl and to a smaller extent, 2,3-pentadione, acetic acid, and butanoic acid were involved in the antifungal activity of L. paracasei DGCC 2132 . In another study, Le Lay et al (2016) [ 179 ] showed that lactic, acetic, and propionic acids, ethanol and hydrogen peroxide, as well as other compounds present at low levels such as dl -β-phenyllactic, dl -β-hydroxyphenyllactic, azelaic, and ( S )-(−)-2–hydroxyisocapric acids were responsible for the antifungal activity of lactobacilli and propionibacteria CFS active against spoilage molds in bakery products.…”
Section: Action Mechanisms Of Antifungal Microorganismsmentioning
confidence: 99%
“…These authors observed an altered transcription of a large variety of cellular functions involved in metabolism, transport, signaling, ergosterol biosynthesis, and cell stress, including that of LaeA, a global regulator of secondary metabolism. More recently, Mieszkin et al (2017) [ 175 ] investigated the action mechanisms involved in the bioprotective effect of L. harbinensis K.V9.3.1.Np against Y. lipolytica in fermented milk. The CFS obtained after milk fermentation by yogurt starters in co-culture with the bioprotective strain had a fungistatic rather than a fungicidal effect accompanied with a significant loss of cultivability in the studied yeast.…”
Section: Action Mechanisms Of Antifungal Microorganismsmentioning
confidence: 99%